The Collocation Method For Fourth Order Fuzzy Boundary Value Problems (Journal of the College of Basic Education, 2022)
In this paper, the collocation method is considered to solve the nonhomogeneous for fourth order fuzzy boundary value problems, In which the fuzziness appeared together in the boundary conditions and in the nonhomogeneous term of the differential equation. The method of solution depends on transforming the fuzzy problem to equivalent crisp problems using the concept of α-level sets.